A Mini-Review on Hydrogen-Rich Syngas Production by Thermo-Catalytic and Bioconversion of Biomass and Its Environmental Implications - Ayodele, Bamidele V.; Mustapa, Siti Indah; Tuan Abdullah, Tuan Ab Rashid B.; Salleh, Siti Fatihah b. (Frontiers in Energy Research, 2019)
The thermo-catalytic and biochemical conversion of biomass to hydrogen-rich syngas has been widely reported with less emphasis on the environmental implications of the processes. This mini-review presents an overview of different thermo-catalytic route of converting biomass to hydrogen-rich syngas as well as their environmental impact investigated using life cycle assessment methodology. The review revealed that most of the authors employed, biomass gasification, biomass pyrolysis, reforming and fermentative processes for the hydrogen-rich syngas production. Global warming potential was observed as the most significant environmental impact reported in the reviewed articles. The CO2 equivalent emissions were found to varies with each of the processes and the type of feedstock used. Trends from literature show that both thermo-catalytic and biochemical processes have competitive advantages and potential to compete favorable with the existing technology used for hydrogen production. Nevertheless, it cannot be ascertained that these technologies should be excluded from environmental burdens. This mini-review could be a quick guide to future research interest in environmental impact of hydrogen-rich syngas production by thermo-catalytic and biochemical conversion of biomass.